Analysis of Geodetic Positioning as Tool for Monitoring Variations from the Level of a River - Prol, Fabricio dos Santos; Marcato Junior, José; Paranhos Filho, Antonio Conceição (Anuário do Instituto de Geociências, 2017)
Although the GPS (Global Positioning System) has been built for geodetic positioning and navigation, the system enabled analyses a wide number of terrestrial phenomena. In this way, new applications have emerged in recent years. To expand the applications for the GPS users, this work explores the possible connections between changes in a river level in comparison to the precise estimated altitudes from geodetic solutions, particularly associated with a GPS station. The precise geodetic solutions from SIRGAS (Sistema de Referência Geocêntrico para as Américas) were compared with the hydrological observations made by ANA (Agência Nacional de Águas). Two stations were selected and they are located in the Pantanal complex, where is a region with an expansive area of wetland. The results present a strong anti-correlation behavior, showing that the geodetic positioning can be used in monitoring changes in the level of a river.